EFEKTIVITAS APLIKASI WORDWALL PADA HASIL BELAJAR IPS SISWA - Wiwik Wiji Astuti; Muh. Yahya; Mustansir Mustansir; Irna Santrianti; Syamsinar Syamsinar (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2023)
In the era of global society, we are required to balance advances in technology and knowledge, the form of application is to develop their hard skills and soft skills through developed technology. One form of its implementation in the world of education is the use of wordwall applications in social studies to improve various thinking and mathematical abilities. This study aims to determine the effectiveness of wordwall applications on students’ learning outcome. The method used in this research is SLR (Systematic Literature Review) in which researchers collect articles related to wordwall applications with a publication period of 2021-2022, systematic abilities and social studies to be documented and reviewed as supporting data for this research. Based on this research the results are; 1) Definition of the wordwall application, purpose, and its important role in the era of global society 5.0, especially in the field of education, 2) There is evidence that there is a positive response from students in learning social studies through the wordwall application, 3) There is a significant influence on the use of the wordwall application on increasing students’ learning outcome.